The establishment of methods for free PAR generation and PAR reader detection. (June 2018) - Ke, Yueshuang; Wang, Ke; Xu, Hui; Wang, Chenxin; Zhang, Jing; Zeng, Xianlu; Wang, Ruoxi; Boldogh, Istvan; Ba, Xueqing
Abstract: Poly (ADP-ribose) polymerase 1 (PARP1) is a DNA damage sensor that catalyzes the poly (ADP-ribose) (PAR) onto a variety of target proteins, such as histones, DSB repair factors and PARP1 itself under consumption of NAD + . Besides, PARP1 can affect a variety of proteins in noncovalent modification manner to carry out specific cellular functions. Here, we established a method to generate non-radiolabeled free PAR by PARG moderately cleaving PAR from autoPARylated PARP1, and utilized dot-blot assay to determine the interaction between free PAR and interested proteins. The methods to generate free PAR and detect the noncovalent interactions between proteins and free PAR are nonradioactive and convenient, which will facilitate the studies to explore the significance of PAR reading in various biological processes. Highlights: Set up of a rapid, convenient and nonradioactive method to generate and detect free PAR. RNA binding protein HuR, which can be covalently PARylated by PARP1, is not a PAR reader. This method will facilitate the studies to explore the significance of PAR reading in various biological processes.